Controlling posture during grasping with different optical flow conditions - Rodrigues, Sérgio Tosi (2015)
Many environmental aspects such as the optical flow and one's own movement can affect posture stabilization. However, little is known about how these two features can be combined as participants maintain upright stance during grasping actions. Therefore, the purpose of this study was to examine the effects of moving room discrete movements (approaching to or moving back from participants) combined with grasping an object on postural control stability. Twelve participants stood upright inside a moving room, moved discretely approaching or moving away from the participants, as they had to remain still or grasping a stationary or an approaching ball. Body displacement and correlation coefficient values were obtained during the movement of the moving room and mean sway amplitude were used to infer postural stability before and after room's movement. Results indicated that grasping and movement of the moving room disrupted and induced body sway, even after the grasping action, however in those conditions in which optical flow was created, due to the moving room and moving ball, postural sway was less pronounced. Based upon these results, we can suggest that in those conditions that structured optical flow is available, even when posture might be destabilized due to one's own movement, postural control takes advantage of the optical flow to maintain postural equilibrium.